Determinants of offer of goats and sheep farmers in the municipality of family Parnamirim - PE - Edder de Carvalho SÃ (2012)
The analysis of the supply of goats and sheep by farmers in the municipality of Parnamirim - PE was structured in this research, the reasons for the identification of the determinants of sales of animals and how these variables relate. The weather proved to be the main reason for holding the Sheep and Goat Farming, with most families having vast experience in the activity, average of fifteen to twenty years of operation. The credit and technical assistance support figured as the highest political level of efficiency by the perception of farmers, though still not comprehensive. The use of real estate ventures to explorers for these animals was marked by the presence of owners and leaseholders having equity relative weights among the other types of use. Old and recurring problem is still present, lack of regularization of land in the municipality. Family agriculture and the Sheep and Goat Farming have peculiar characteristics that are vital to show the adequacy of models for exploration and development of policies to support the activity.